2021
DOI: 10.3390/v13050725
|View full text |Cite
|
Sign up to set email alerts
|

Novel Virulent Bacteriophages Infecting Mediterranean Isolates of the Plant Pest Xylella fastidiosa and Xanthomonas albilineans

Abstract: Xylella fastidiosa (Xf) is a plant pathogen causing significant losses in agriculture worldwide. Originating from America, this bacterium caused recent epidemics in southern Europe and is thus considered an emerging pathogen. As the European regulations do not authorize antibiotic treatment in plants, alternative treatments are urgently needed to control the spread of the pathogen and eventually to cure infected crops. One such alternative is the use of phage therapy, developed more than 100 years ago to cure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 58 publications
(80 reference statements)
1
10
0
Order By: Relevance
“…5 ) with a GC content of 67.3% that is similar to the host S. maltophilia GC content. BLASTn analysis of AXL1 showed high relatedness to phages in the genus Pamexvirus , most closely aligning to Xanthomonas phage Bosa 20 with 91.01% identity over 97% of the genome. Among this genus, in order of percent identity to AXL1, are Xanthomonas phage Xp12 21 , Stenotrophomonas phage DLP4 7 , Xanthomonas phage Xoo-sp2 22 , and the Pseudomonas phages AAT-1 23 , PaMx28, and PaMx74 24 .…”
Section: Resultsmentioning
confidence: 99%
“…5 ) with a GC content of 67.3% that is similar to the host S. maltophilia GC content. BLASTn analysis of AXL1 showed high relatedness to phages in the genus Pamexvirus , most closely aligning to Xanthomonas phage Bosa 20 with 91.01% identity over 97% of the genome. Among this genus, in order of percent identity to AXL1, are Xanthomonas phage Xp12 21 , Stenotrophomonas phage DLP4 7 , Xanthomonas phage Xoo-sp2 22 , and the Pseudomonas phages AAT-1 23 , PaMx28, and PaMx74 24 .…”
Section: Resultsmentioning
confidence: 99%
“…Di Lallo et al (2014) [ 42 ] isolated phage ΦPSA2, whose bacterial host is the causal agent of kiwifruit bacterial canker, from a municipal sewage sample. Clavijo-Coppens et al (2021) [ 43 ] have reported that phages able to infect the plant pathogens Xylella fastidiosa and Xanthomonas albilineans were isolated from surface and sewage waters, but not from infected plants.…”
Section: Discussionmentioning
confidence: 99%
“…Xanthomonas albilineans ( Xa ), strain CFBP2523 (GenBank accession number, MDCB00000000), was purchased from the “French Collection of Plant-associated Bacteria” (Angers, France) and was grown on LPGA for 2 days at 28 °C [ 26 ]. Xylella fastidiosa subsp.…”
Section: Methodsmentioning
confidence: 99%
“…Due to the particular nature of Xf, and to establish an approximate starting concentration of peptides with which Xf cells could be afterward challenged, prior screening was performed using the surrogate Xa , a phylogenetically close and relatively swift-growing organism [ 26 ].…”
Section: Methodsmentioning
confidence: 99%